Sialomes and Mialomes: A Systems-Biology View of Tick Tissues and Tick-Host Interactions - Chmelař, Jindřich; Kotál, Jan; Karim, Shahid; Kopacek, Petr; Francischetti, Ivo M B; Pedra, Joao H F; Kotsyfakis, Michail (Trends in parasitology, 2016)
Tick saliva facilitates tick feeding and infection of the host. Gene expression analysis of tick salivary glands and other tissues involved in host-pathogen interactions has revealed a wide range of bioactive tick proteins. Transcriptomic analysis has been a milestone in the field and has recently been enhanced by next-generation sequencing (NGS). Furthermore, the application of quantitative proteomics to ticks with unknown genomes has provided deeper insights into the molecular mechanisms underlying tick hematophagy, pathogen transmission, and tick-host-pathogen interactions. We review current knowledge on the transcriptomics and proteomics of tick tissues from a systems-biology perspective and discuss future challenges in the field.
Keywords: Systems Biology; interakce hostitele a parazita; Host-Parasite Interactions; tick-borne pathogens; Animals; Ticks; next-generation sequencing; systems biology; Proteome; proteom; zvířata; Humans; sialomes; klíšťata; systémová biologie; lidé; Transcriptome; transkriptom